Advances in Diagnostic Bronchoscopy - Yi-Cheng Shen (MDPI AG, 2021)
The increase in incidental discovery of pulmonary nodules has led to more urgent requirement of tissue diagnosis. The peripheral pulmonary nodules are especially challenging for clinicians. There are various modalities for diagnosis and tissue sampling of pulmonary lesions, but most of these modalities have their own limitations. This has led to the development of many advanced technical modalities, which have empowered pulmonologists to reach the periphery of the lung safely and effectively. These techniques include thin/ultrathin bronchoscopes, radial probe endobronchial ultrasound (RP-EBUS), and navigation bronchoscopy—including virtual navigation bronchoscopy (VNB) and electromagnetic navigation bronchoscopy (ENB). Recently, newer technologies—including robotic-assisted bronchoscopy (RAB), cone-beam CT (CBCT), and augmented fluoroscopy (AF)—have been introduced to aid in the navigation to peripheral pulmonary nodules. Technological advances will also enable more precise tissue sampling of smaller peripheral lung nodules for local ablative and other therapies of peripheral lung cancers in the future. However, we still need to overcome the CT-to-body divergence, among other limitations. In this review, our aim is to summarize the recent advances in diagnostic bronchoscopy technology.